2012
DOI: 10.1158/0008-5472.can-12-0851
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic Tumor Cell Death Induced by Chemoradiotherapy in Patients with Esophageal Squamous Cell Carcinoma

Abstract: Although it has been shown that chemoradiotherapy may induce immunogenic cell death, which could trigger T-cell immunity mediated by high-mobility group box 1 protein (HMGB1) and calreticulin, there is still limited information to support this theory directly in a clinical setting. In the present study, we evaluated antigen-specific T-cell responses against six cancer-testis antigens in peripheral blood lymphocytes from patients with esophageal squamous cell carcinoma (ESCC) receiving chemoradiation. Expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(166 citation statements)
references
References 31 publications
8
157
1
Order By: Relevance
“…15 Apoptosis occurs ubiquitously in normal tissues and causes 'quiet' cell death that uses phosphatidylserine (PS) as an 'eat-me' signal to be quickly recognized by peripheral APCs. Although apoptotic cell death has been historically considered to be nonimmunogenic, 16 recent studies unraveled that several antineoplastic agents, including doxorubicin, 1,17 oxaliplatin, 18,19 cisplatin, 20 and irradiation, 21,22,23 can trigger immunogenic apoptosis. 2 Mechanistically, the immunogenic apoptotic bodies induced by exposure to doxorubicin are sensed by APCs through their TLR-2/TLR-9-MyD88 signaling pathways.…”
Section: Apoptotic Cell Death As Icdmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Apoptosis occurs ubiquitously in normal tissues and causes 'quiet' cell death that uses phosphatidylserine (PS) as an 'eat-me' signal to be quickly recognized by peripheral APCs. Although apoptotic cell death has been historically considered to be nonimmunogenic, 16 recent studies unraveled that several antineoplastic agents, including doxorubicin, 1,17 oxaliplatin, 18,19 cisplatin, 20 and irradiation, 21,22,23 can trigger immunogenic apoptosis. 2 Mechanistically, the immunogenic apoptotic bodies induced by exposure to doxorubicin are sensed by APCs through their TLR-2/TLR-9-MyD88 signaling pathways.…”
Section: Apoptotic Cell Death As Icdmentioning
confidence: 99%
“…However, the observation that the tumor microenvironment tends to be pro-oxidative 63 implies that a therapeutic approach using antioxidants to decrease ROS production would be favorable to stimulate antitumor immunity. Importantly, many anticancer agents, including chemotherapy, 30 radiation, 22 or oncolytic viruses, 9,64,65 have been shown to induce HMGB1 release from cancer cells, highlighting the significance of further addressing the mechanism of how these modalities affect the redox status of HMGB1.…”
Section: Hmgb1mentioning
confidence: 99%
“…22 It turned out that the unsuspected ability of doxorubicin (an anthracycline employed for the treatment of various carcinomas) to trigger ICD as a standalone intervention, hence converting dying cancer cells into a vaccine that is efficient in the absence of adjuvants, is shared by a relatively restricted set of lethal triggers. [28][29][30][31][32][33] These include, but perhaps are not limited to, mitoxantrone and epirubicin (2 other anthracyclines currently used in the clinic), [34][35][36][37] bleomycin (a glycopeptide antibiotic endowed with antineoplastic properties), 38 oxaliplatin (a platinum derivative generally employed against colorectal carcinoma), [39][40][41][42] cyclophosphamide (an alkylating agent approved for the treatment of neoplastic and autoimmune conditions), [43][44][45][46][47][48] etoposide (a topoisomerase inhibitor currently used for the treatment of several neoplasms) combined with the chemical inhibitor of glycolysis 2-deoxyglucose, 49,50 patupilone (a microtubular inhibitor that has not yet been approved for use in humans), [51][52][53] septacidin (an antifungal antibiotic produced by Streptomyces fibriatus) 54,55 specific forms of radiation therapy, 34,[56][57][58][59][60][61][62][63][64] photodynamic therapy (a clinically approved antican...…”
Section: Introductionmentioning
confidence: 99%
“…The authors previously reported that malnutrition or hypoalbuminemia correlates well with immune suppression, systemic inflammation and suppression of cell-mediated immunity (34)(35)(36)(37)(38). Systemic inflammation may underlie these conditions, which are prominent in patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%